2014
DOI: 10.15446/agron.colomb.v32n1.42060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high iron doses (Fe2+) on the growth of broccoli plants (Brassica oleracea var. Italica)

Abstract: Tests were carried out under greenhouse conditions in Tunja (Colombia) in order to evaluate the effect of Fe2+ toxicity on the growth of broccoli plants. 'Legacy' hybrid Brassica oleracea var. Italica plantlets were grown in glass containers with a nutritive solution. Iron sulfate was added to the substrate in order to produce excess iron at concentrations of 100 and 200 mg L-1; a control without iron sulfate applications was used. The following evaluations were made: leaf area, total dry weight of the plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Elevated Fe 2+ concentration in the substrate strongly decreases the radicle development (Rodrigues Filho et al, 2020). Moreover, Peña‐Olmos et al (2014) confirmed this decrease while working on broccoli ( Brassica oleracea var. italica ), they further documented that a higher dose of Fe 2+ (50 mg L −1 ) increases the lipid peroxidation particularly in radicle zone, which results in stunted growth and lowers dry weight production, this decrease in radical growth causes a severe effect on all the development‐related processes including loss of radicle hairs and reduction in its volume, which drastically reduce the total water content of the plant (De Dorlodot et al, 2005).…”
Section: Fe Toxicity and Its Effect On Various Plant Attributesmentioning
confidence: 86%
See 4 more Smart Citations
“…Elevated Fe 2+ concentration in the substrate strongly decreases the radicle development (Rodrigues Filho et al, 2020). Moreover, Peña‐Olmos et al (2014) confirmed this decrease while working on broccoli ( Brassica oleracea var. italica ), they further documented that a higher dose of Fe 2+ (50 mg L −1 ) increases the lipid peroxidation particularly in radicle zone, which results in stunted growth and lowers dry weight production, this decrease in radical growth causes a severe effect on all the development‐related processes including loss of radicle hairs and reduction in its volume, which drastically reduce the total water content of the plant (De Dorlodot et al, 2005).…”
Section: Fe Toxicity and Its Effect On Various Plant Attributesmentioning
confidence: 86%
“…Becker and Asch (2005) reported that excess Fe 2+ concentrations in the leaves and stems results in early defoliation, and consequent decrease in growth, and in some cases complete cessation of growth in different organs of the plants. According to Peña‐Olmos et al (2014), a progressive decrease in dryness of roots, leaves, and stem supported the higher Fe 2+ flow toward the interior of plant. Nenova (2006) also opined that weight of pea ( Pisum sativum ) reduces with increasing Fe 2+ concentration up to 40 mg L −1 at 41 days after sowing (DAS).…”
Section: Fe Toxicity and Its Effect On Various Plant Attributesmentioning
confidence: 90%
See 3 more Smart Citations